Current situation on trans fatty acids occurrence in processed foods commercialized in Portugal - Albuquerque, T.G. (2019)
Processed foods are generally recognized as a source of salt, fat and sugar. An excessive intake of these nutrients is perceived as the leading reason for an increased risk in the development of several chronic diseases. From a public health point of view, nutritional quality of foods, dietary intake and mortality are closely linked.